PDE2 Inhibits PKA-Mediated Phosphorylation of TFAM to Promote Mitochondrial Ca2+-Induced Colorectal Cancer Growth - Zhao, Yilin; Wang, Yaya; Zhao, Jing; Zhang, Zhaohui; Jin, Mingpeng; Zhou, Feng; Jin, Chao; Zhang, Jing; Xing, Jinliang; Wang, Nan; He, Xianli; Ren, Tingting (Frontiers in Oncology, 2021)
Growing evidence indicates that the dysregulation of mitochondrial calcium (Ca2+) plays a critical role in the growth of tumor cells, including colorectal cancer (CRC). However, the underling mechanism is not fully elucidated. In this study, the regulatory effects of mitochondrial Ca2+ on phosphodiesterase 2 (PDE2)/cAMP/PKA axis and the phosphorylation of mitochondrial transcription factor A (TFAM) as well as the growth of CRC cells were systematically investigated both in vitro and in vivo. Our findings demonstrated that MCU-induced mitochondrial Ca2+ uptake activated mitochondrial PDE2 in CRC cells. Moreover, overexpression MCU in CRC led to a 1.9-fold increase in Ca2+ uptake compared to control cells. However, knockdown of MCU resulted in 1.5-fould decrease in Ca2+ uptake in mitochondria compared to the controls. Activation of mitochondrial PDE2 significantly inhibited the activity of mitochondrial protein kinase A (PKA), which subsequently leads to decreased phosphorylation of TFAM. Our data further revealed that PKA regulates the phosphorylation of TFAM and promotes the degradation of phosphorylated TFAM. Thus, TFAM protein levels accumulated in mitochondria when the activity of PKA was inhibited. Overall, this study showed that the overexpression of MCU enhanced CRC growth through promoting the accumulation of TFAM proteins in mitochondria. Conversely, knockdown of MCU in CRC cells resulted in decreased CRC growth. Collectively, these data suggest that the mitochondrial Ca2+-activated PDE2/cAMP/PKA axis plays a key role in regulating TFAM stability and the growth of CRC cells.